Value Chain Analysis of Corn Commodity Supply Chain - Rasyid, Abdul (Budapest International Research and Critics University, 2021)
This research aims to analyze the supply chain, value chain and added value obtained from corn supply chain actors. This research was conducted in Taluditi District, Pohuwato Regency, Gorontalo Province using qualitative and quantitative analysis. The results of this study indicate that the supply chain value of corn commodities in the sub-district consists of supply chain actors. The supply chain actors involved are the main actors and supporting actors. The supply chain has a dynamic nature but involves three constant flows, namely the flow of products or goods, the flow of information and the flow of money. The value chain is a value activity divided into two types, namely the main activity and the supporting activity. The main actors in the corn value chain analysis include farmers, local traders and companies. The added value of corn commodity is the added value of a commodity because it undergoes processing, storage, transportation in a production process. The added value calculated in the value chain analysis is the added value obtained from each value chain actor involved in the corn harvest, namely the value added analysis of corn farmers, analysis of the added value of local traders or large collections and analysis of company value added. The results of this study are the corn value chain based on quantitative analysis, the highest margin from value chain actors is local traders of 377,500 Kg or 36.17%, the added value based on the hayami method on value chain actors shows that the main value chain actors who obtain the greatest added value are farmers and companies because it is classified as a value added ratio of >50%.